BREASTFEEDING IN PUBLIC: THE INTERSECTION OF BIOLOGY AND SEXUALITY - Marinda P.D. Ghaisani; Dewi H. Susilastuti (International Journal of Humanity Studies (IJHS), 2022)
Breastfeeding is an infant feeding method recommended by health practitioners. Many women see it as an advantageous infant feeding method. Moreover, they perceive it as their right to provide the best for their children, and it has been legally protected. Unfortunately, not everybody looks at breastfeeding in public in a positive light. The United States of America is the bastion of individual rights.  Ironically women who exercise their right to breastfeed in public often experiment objections from others. Those who protest against breastfeeding in public argue that the act is inappropriate as it involves breasts. Indeed, breasts have two functions: biological and sexual, but breasts’ sexual function often overshadows its biological function. The objection to breastfeeding in public puts women in an uncomfortable position that is fraught with disagreements. According to the theory of intimate citizenship, multiple voices regarding breastfeeding in public breed conflict. There is a tension between personal concerns of breastfeeding mothers and discomfort of some elements of the public. In addition, there is a silent agreement that breastfeeding mothers are expected to resolve these competing needs.